Karakteristik Organoleptik dan Kimia Pukis Tepung Talas (Xanthosoma Sagitifolium) yang Difortifikasi Dengan Tepung Kulit Udang Vaname (Ditopenaeus Vannamei) : (Organoleptic and Chemical Characteristics of Taro Flour Pukis (Xanthosoma Sagitifolium) Flour Fortified with Vaname Shrimp Skin Flour (Ditopenaeus Vannamei)) - Megawati Elu; Rahim Husain; Sutianto Pratama Suherman (Transbahasa, 2023)
The research aimed to determine the organoleptic and chemical quality of pukis cake. The treatment of this research was the addition of shrimp shell powder for 15gr, 20gr, and 25gr to pukis cake. Additionally, the parameters tested were organoleptic characteristics, namely appearance, aroma, color, taste, and texture which were analyzed using the Kruskal-Wallis test. The treatments with significant effects were further tested with Duncan’s Multiple Range test to determine differences in treatment. On the other hand, the chemical characteristics observed werw moisture content, fat content, ash content, protein content, and calcium content. The results of Duncan’s Multiple Range test indicated that the treatment of the pukis formulation with different fortification of shrimp shell powder resulted in significantly different organoleptic characteristics off appearance, aroma, color, taste, and texture. At the same time, the fortification of shrimp shell powder affected the chemical characteristics of pukis cake, namely the water content of around 20.64%, ash content of 1.68%, fat content of 5.85%, protein content of 8.745%, and calcium content of 21.45 mg/kg. the best treatment, according to the panelist’s assessment of pukia cake, was treatment A, namely 15gr of shrimp shell powder.